ANALYSIS AND COMPARISON OF LINGUISTIC FEATURES OF GENDER COMMUNICATION ON THE EXAMPLE OF ITALIAN AND UZBEK LITERATURE (Eureka Journal of Language, Culture & Social Change, 2026)
The article is devoted to the analysis and comparison of linguistic features of gender communication in Italian and Uzbek literature in the context of intercultural interaction. Gender is considered as a cognitive-cultural phenomenon manifested in linguistic structures, speech behavior and artistic discourse.
Keywords: Gender communication, intercultural communication, Italian literature, Uzbek literature, linguistic representation of gender, gender concepts, gender metaphor, comparative analysis, artistic discourse, cultural differences